An overview of potential of natural compounds to regulate epigenetic modifications in colorectal cancer: a recent update - Susmita Roy; Dikshita Deka; Suresh Babu Kondaveeti; Pavithra Ayyadurai; Sravani Siripragada; Neha Philip; Surajit Pathak; Asim K. Duttaroy; Antara Banerjee (Epigenetics)
Colorectal cancer (CRC) remains an alarming global health concern despite advancements in treatment modalities over recent decades. Among the various factors contributing to CRC, this review emphasizes the critical role of epigenetic mechanisms in its pathogenesis and progression. This review also describes the potential role of natural compounds in altering the epigenetic landscape, focused mainly on DNA methylation, histone modification, and non-coding RNAs. Publications from the previous five years were searched and retrieved using well-known search engines and databases like PubMed, Google Scholar, and ScienceDirect. Keywords like CRC/colorectal cancer, CAC/Colitis associated CRC, inflammasomes, epigenetic modulation, genistein, curcumin, quercetin, resveratrol, anthocyanins, sulforaphane, and epigallocatechin-3-gallate were used in various combinations during the search. These natural compounds predominantly affect pathways such as Wnt/β-catenin, NF-κB, and PI3K/AKT to suppress CRC cell proliferation and oxidative stress and enhance anti-inflammation and apoptosis. However, their clinical use is restricted due to their low bioavailability. However, multiple methods exist to overcome challenges like this, including but not limited to structural modifications, nanoparticle encapsulations, bio-enhancers, and novel advanced delivery systems. These methods improve their potential as supportive therapies that target CRC progression epigenetically with fewer side effects. Current research focuses on enhancing epigenetic targeting to control CRC progression while minimizing side effects, emphasizing improved specificity, bioavailability, and efficacy as standalone or synergistic therapies.